Good faith in contract law: from the general to the particular and from the particular to the general - Tsarova, Liudmila V.; Kupreychik, Alexander A. (Journal of the Belarusian State University. Law, 2023)
The study aims to identify the specifics of the development of the principle of good faith in the contract law of Belarus by analysing its formation and comparing with the approaches to the consolidation and implementation of the principle in foreign jurisdictions and in international contract law. The article concludes that there is no direct correlation between the model of normative fixing of the good faith principle and its implementation in practice. The study has shown that the real effect of the principle of good faith is ensured not so much by its literal wording, as by the legal traditions of a particular legal order and judicial activism.
Keywords: principle of good faith; contract law; international contract law; estoppel